The Syntactic-Stylistic Devices in the Texts of Constitutions - Hakobyan, Anna (Armenian Folia Anglistika, 2008)
Regardless of certain common linguostylistic characteristics typical of all formal texts, each domain, however, possesses a set of features that is specific to it only. In this regard, the linguistic factor in the perception of the constitution is of certain interest. The presence of a number of linguo-stylistic peculiarities can be explained by the communicative function of the language which obtains certain importance here.The article can interest both a linguist and a lawyer, since the knowledge of the peculiarities of the official style and their appropriate application is necessary to ensure successful work in legal procedures.